Performance Analysis of Public Services of The Government of Malalayang District, Manado City - Poluakan, Giovanni Gerardus; Lumingkewas, Lexi; Dilapanga, Abdul Rahman (Technium Social Sciences Journal, 2021)
Articles have tried to find its analysis performance of public services in the District Malalayang Manado City. The analysis focused on making the deed of the land where the services are in grades. The quality of service is higher in comparing the service. The research seeks to provide reflection and examples to other sub-district offices and government agencies that have duties and functions to serve the community so that they are motivated to correct deficiencies in their agencies. The method of research is using the approach of descriptive qualitative. The collection of data is complete (holistic) relevant to the focus, the formulation of the problem and purpose. Using three techniques were prevalent in the research qualitative, namely: (1) interviews depth, (2) participation observation, and (3) study the documentation. This study uses an interactive model analysis from Miles and Huberman, consisting of analysis components: data reduction, data presenting, and conclusion drawing. The study results show that factors support and inhibiting the implementation of the services to the public at the office of the District Malalayang. Factor inhibitors such as (1) the lack of a source of power employees and is still a lack of facilities and infrastructure, the factors supporting that (1) the spirit of the awarded employees of each other, (2) hold a meeting of coordination or some sort of evaluation every three months. (3) provide planting awareness of serving the community. (4) Facility in the form of tools helps to facilitate the process of service.